PENERAPAN STRATEGI PEMBELAJARAN TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 46 GAJAH SAKTI KEC. MANDAU - Nasuha, Nasuha; Syahrilfuddin, Syahrilfuddin; Hamizi, Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the result of fourth-grade students learn science (IV) SDN 46 Gajah Sakti is still low with an average value of 60.5 KKM 70. The purpose of this research is to improve student learning outcomes fourth grade (IV) SDN 46 Elephants Way with the application of learning strategies Peer Tutor. Penelittian this is a class action with two cycles in the second half of 2014/2015. Before applying the Learning Strategies Peer Tutor average value of 60.5, after applying the Learning Strategies Peer Tutor, UH I is 69.4 which is an increase of 60% from the base score with an average of 60.5. UH II is 75.4 which increased 80%. Activity teachers with the implementation of Learning Strategy Peer tutoring first dipertemuan first cycle was 50% (enough categories), and a second meeting is 60% (good categories) in the second meeting, which increased by 10 points. In the second cycle, the first dipertemuan teacher activity was 80% (good categories) increased 15 points of the second meeting of the first cycle. Teacher activity to 90% (very good). In the second meeting, which increases 10 points. The first student activity dipertemuan first cycle was 50% (enough categories), and 80% (both categories). In the second cycle, the first dipertemuan student activity was 80% (good categories) increased 10 points. The second meeting of the second cycle was 90% (very good). Implementation of Learning Strategy Peer tutoring can enhance the results of the fourth grade students of SDN 46 Gajah Sakti district. Saber.Keywords: Peer Tutor Learning Strategy, Learning Outcomes IPA